A Novel Partogram for Stages 1 and 2 of Labor Based on Fetal Head Station Measured by Ultrasound: A Prospective Multicenter Cohort Study - Haberman, Shoshana; Atallah, Fouad; Nizard, Jacky; Buhule, Olive; Albert, Paul; Gonen, Ron; Ville, Yves; Paltieli, Yoav (American Journal of Perinatology, 2020)
Objective This study was aimed to describe continuous labor curves, including second stage, based on fetal head station.Study Design We performed a prospective multicenter cohort study. The inclusion criteria were women with singleton uncomplicated cephalic term pregnancies in labor, who delivered vaginally. We used a device that combines ultrasound imaging with position-tracking technology to monitor the head station noninvasively throughout labor. We collected data on demographics, labor parameters, and delivery and neonatal outcomes.Results A total of 613 women delivered vaginally, 327 (53.3%) were nulliparous, while 286 (46.7%) were multiparous. Time to delivery (TTD) diminished progressively with descent of the fetal head. When the head is engaged, the labor curve of multiparous women demonstrated a more prominent downward shift in curve as compared with nulliparous women. When comparing multipara and nullipara at engagement level, the median TTD was 1 and 1.62 hours, respectively. In 95% of women with unengaged head during the second stage, TTD of nulliparous and multiparous women were less than 3.8 and 3 hours, respectively.Conclusion While current labor curves end at full dilatation, the described curves were developed throughout stages 1 and 2 of labor. The TTD, according to the station curves, shows an acceleration of labor, once passed the engagement level, especially in multiparous women.
Keywords: fetal head station; labor curve; ultrasound in labor; labor progression; LaborPro system